(3HgLI GdRef aj JGQjN SGOGJ YdeGA Gdjefs - (3MSjf Hf YHO GdQMef Hf eMeO, HOQGdOjf GdeYQha HGHf GdCgOds; (3GdHgGA jhSa Hf jYbhH GdLfOj,J (B732 (3g` s
(3ChdgG (B:s
(3hef eOjfI aTGd , hgj Ge bQi hGOi ReY s
(3BNQgG (B:s
(3hbO JMQjJ ajgG HMSH GdEecGf, aef JMbb NddG adjUdM s
(3GfXQ Qbe (B979 (3JGQjNs
(3fSNI KGfjI hGdehLhO efg bWYI ef BNQgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJGQjNs